2021
DOI: 10.1016/j.ajur.2020.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Robotic renal and adrenal oncologic surgery: A contemporary review

Abstract: Robot-assisted surgery has evolved over time. Radical nephrectomy with inferior vena cava thrombectomy is feasible and safe for level I, II and III thrombus in high volume centers. Though it is feasible for level IV thrombus, this procedure needs a multi-departmental co-operation. However, the safety of robot-assisted procedures in this subset is still unknown. Robot-assisted partial nephrectomy has been universally approved and found oncologically safe. Robotic adrenalectomy has been increasingly utilized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Preoperative planning helps determine the success of the RARN/IVCTT, a complicated procedure. Crucial factors to obtain from preoperative imaging include the proximal extent of the thrombus, size of the primary tumor, lymph node status, volume of the thrombus, distance from the hepatic veins, arterialization, and potential caval wall invasion [ 47 , 48 ]. IVC tumor thrombi have the potential to grow rapidly, so it is recommended that imaging be performed or repeated within 1 to 2 weeks of the surgery for precise surgical planning [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative planning helps determine the success of the RARN/IVCTT, a complicated procedure. Crucial factors to obtain from preoperative imaging include the proximal extent of the thrombus, size of the primary tumor, lymph node status, volume of the thrombus, distance from the hepatic veins, arterialization, and potential caval wall invasion [ 47 , 48 ]. IVC tumor thrombi have the potential to grow rapidly, so it is recommended that imaging be performed or repeated within 1 to 2 weeks of the surgery for precise surgical planning [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The indications of RALPN gradually expanded to include complex renal tumors, such as renal hilar and endophytic tumors. Hilar tumors have long been a challenge for surgeons to perform minimally invasive surgery due to their difficult placement 9–12 . Although relevant literature has demonstrated the feasibility and safety of CLPN and RALPN in the treatment of hilar tumors, only surgeons with extensive laparoscopic experience can do CLPN 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in a systematic review of 14 retrospective studies, Lardas et al ., concluded that surgical management of patients with non‐metastatic RCC with IVC thrombus is complex, but potentially curative and acceptable 1 . Surgical procedures in RA‐RN/IVCTT vary depending on the level of thrombus; recently, Seetharam et al ., reported that RA‐RN/IVCTT is feasible and safe for level I, II, and III thrombus in high volume centers 2 . Due to the high levels of surgical complexity and variation, RA‐RN/IVCTT is currently performed solely by well‐experienced surgeons in limited high‐volume centers, and its safety is still unknown.…”
mentioning
confidence: 99%